The effects of biochars from rice residue on the formation of iron plaque and the accumulation of Cd, Zn, Pb, As in rice (Oryza sativa L.) seedlings - Zheng, Rui-Lun; Cai, Chao; Liang, Jian-Hong; Huang, Qing; Chen, Zheng; Huang, Yi-Zong; Arp, Hans Peter H.; Sun, Guo-Xin (Chemosphere (Oxford), 2012)
► Rice biochar reduced Cd, Zn and Pb transport to rice shoots, though increased As. ► Biochars derived from rice straw were more influential than from bran and husk. ► Mechanisms for these effects were identified. ► Biochar increased iron plaque formation, and its capacity to retain Cd and Pb. ► Biochar also influenced the soil pore water solubility of Cd, Zn, Pb and As. A historically multi-metal contaminated soil was amended with biochars produced from different parts of rice plants (straw, husk and bran) to investigate how biochar can influence the mobility of Cd, Zn, Pb and As in rice seedlings (Oryza sativa L.). Rice shoot concentrations of Cd, Zn and Pb decreased by up to 98%, 83% and 72%, respectively, due to biochar amendment, though that of As increased by up to 327%. Biochar amendments significantly decreased pore water concentrations (Cpw) of Cd and Zn and increased that of As. For Pb it depended on the amendment. Porewater pH, dissolved organic carbon, dissolved phosphorus, silicon in pore water and iron plaque formation on root surfaces all increased significantly after the amendments. The proportions of Cd and Pb in iron plaque increased by factors 1.8–5.7 and 1.4–2.8, respectively; no increase was observed for As and Zn. Straw-char application significantly and noticeably decreased the plant transfer coefficients of Cd and Pb. This study, the first to investigate changes in metal mobility and iron plaque formation in rice plants due to amending a historically contaminated soil with biochar, indicates that biochar has a potential to decrease Cd, Zn and Pb accumulations in rice shoot but increase that of As. The main cause is likely biochar decreasing the Cpw of Cd and Zn, increasing the Cpw of As, and increasing the iron plaque blocking capacity for Cd and Pb.